Country Partnership Framework for Mauritius for the Period of FY17-FY21 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
The Country Partnership Framework (CPF) for Mauritius covers FY17-21. The previous Country Partnership Strategy (CPS) was originally intended to cover FY07-13 but was extended through FY15 at the time of the CPS Progress Report. The CPF is informed by the Systematic Country Diagnostic (SCD) that was circulated to the Board in July 2015. Elections in December 2014 led to the formation of a new Government and this CPF is aligned strategically with the Government Programme 2015-2019, Achieving Meaningful Change, that was presented to Parliament on January 27, 2015. The CPF seeks to maximize over a five-year period the comparative advantages of the World Bank Group (WBG), through packages of innovative public and private financing options based on cutting edge global knowledge and experience. The CPS provided strategic support around the Government of Mauritius’ (GoM) four pillars of reform : (i) fiscal consolidation and improving public sector efficiency; (ii) improving trade competitiveness; (iii) improving the business climate; and (iv) democratizing the economy through participation, inclusion and sustainability. The report evaluates the achievements of CPS program outcomes as laid out in the results matrix; assesses the WBG’s performance in designing and implementing the CPS program, and draws lessons for the preparation of the forthcoming Country Partnership Framework (CPF). The CPS pillars were relevant and well aligned in addressing Government priorities and country needs. Flexibility in the design of the strategy facilitated rapid response to changing needs and the Bank was able to respond promptly and effectively to unexpected events such as the triple trade shocks, global financial crisis and political transition.